Changes in streamflow seasonality associated with hydroclimatic variability in the north-central United States among three discrete temporal periods, 1946–2020 - Nancy A. Barth; Harper N. Wavra; Anthony R. Koebele; Steven K. Sando (Journal of Hydrology: Regional Studies)
Study region: North-central United States Study focus: This study uses circular statistics to characterize the seasonal properties of annual maximum (AMS) and peaks-over-threshold (POT) streamflow time series for 841 and 623 selected U.S. Geological Survey (USGS) streamgages, respectively, without regulation or substantial diversion among common 75-, 50-, and 30-year trend periods through water year 2020 (the period from October 1, 2019, through September 30, 2020). A subset of AMS time series with detected change points (abrupt changes) in the median and (or) scale are analyzed on either side of the change point to evaluate changes in their circular statistics. New hydrologic insights for the region: In the 50-year trend period, five regions share common mean flood timing in the AMS and POT partial duration series. Changes from asymmetric distributions to reflective symmetric distributions are detected particularly among the 50- and 30-year trend periods in the northernmost States of Minnesota, North Dakota, and Wisconsin. For the subset of streamgages with abrupt change points in the AMS, regional patterns of changes in seasonality are detected between the period of records before and after the change point. These findings can inform decisions related to the AMS used for flood frequency and potential mixed population analyses and flood control operations that may be affected by changes in when seasonal events occur, how long seasonal events last, and the long-term variability in the intensity and frequency of seasonal events.